Prevention of Porphyromonas gingivalis-Induced Oral Bone Loss following Immunization with Gingipain R1 - Gibson, Frank C. (American Society for Microbiology, 2001)
The arginine gingipains RgpA and RgpB of Porphyromonas gingivalis are well-documented virulence factors of this organism. Structurally, RgpA and RgpB have nearly identical catalytic domains, while RgpA possesses an additional hemagglutinin domain. In this study, we examined the abilities of these proteins to elicit protection against P. gingivalis-mediated oral bone loss in a murine oral challenge model. Mice immunized subcutaneously with heat-killed P. gingivalis or purified RgpA or RgpB possessed elevated levels of P. gingivalis-specific immunoglobulin G; however, only the animals immunized with P. gingivalis whole cells or RgpA were protected from maxillary bone loss. These data suggest that immunization with RgpA stimulates the production of hemagglutinin domain-specific antibodies, which contribute to the prevention of P. gingivalis-mediated periodontal disease.